ANALYSIS OF LANGUAGE STYLE IN NOVEL DIALOGUE: THE MAZE RUNNER - Lia Hidayati; Diani Syahputri; Linda Astuti Rangkuti (EXCELLENCE: Journal of English and English Education, 2022)
Language style can be found in any form such as in daily conversation, magazine, newspaper, short story, novel, etc. Language style may refer to the writing style used by the author or writer as the way or technique chosen upon sentence structure, word choice, and tone. This study took novel entitled The Maze Runner as the source of data. The objective of conducting this study was to analyze the language styles used in the dialogue of the novel. There were 260 pages in total. The data collection was limited only from page 1 to 100. The design used in this study was descriptive qualitative. The data were collected by reading the novel, analyzed the types of language style, and tabulated the obtained data. The steps used to analyze the data such as identified, listed, and classified the types of language style, counted the percentage, obtained the dominant language styles, described the findings, and displayed data in table. There were 126 dialogues which were analyzed. The findings showed that there were 4 types of language style used in the dialogue. They were colloquial, casual, slang, and consultative style. The percentage obtained such as colloquial style with 55 or 44%, casual style with 37 or 29.36%, slang style with 27 or 21.42%, and consultative style with 7 or 5.5%. From this percentage, it was obvious that the most dominant style used by the author of the novel was colloquial style.